Restlessness and an Increased Urge to Move (Drive for Activity) in Anorexia Nervosa May Strengthen Personal Motivation to Maintain Caloric Restriction and May Augment Body Awareness and Proprioception: A Lesson From Leptin Administration in Anorexia Nervosa - Casper, Regina C. (Frontiers in Psychology, 2022)
Anorexia nervosa (AN), a disorder of voluntary food restriction leading to severe weight loss in female adolescents, remains an enigma. In particular, the appropriation of the starved thin body into the self-concept in AN is a process insufficiently researched and still poorly understood. Healthy humans undergoing starvation experience a slowing of movements and avoid voluntary exercise. By contrast, AN tends to be not infrequently associated with voluntary, sometimes excessive and/or compulsive exercise. Such deliberate exercise, not reported in starvation seems to be facilitated by an increased urge for movement and physical restlessness, particular to AN. The increased urge to move would reflect spontaneous daily activity, the energy expended for everything that is not sleeping, eating, or voluntary exercise. Our hypothesis is that the starvation-induced increased urge to move and restlessness may promote the development of AN. Reversal of the fasting state, by either high caloric food or by leptin administration, would be expected to reduce restlessness and the increased urge to move along with improvement in other symptoms in AN. This review explores the idea that such restless activation in AN, in itself and through accelerating body weight loss, might foster the integration of the starving thin body into the self-concept by 1) enhancing the person’s sense of self-control and sense of achievement and 2) through invigorating proprioception and through intensifying the perception of the changing body shape. 3) Tentative evidence from studies piloting leptin administration in chronic AN patients which support this hypothesis is reviewed. The findings show that short term administration of high doses of leptin indeed mitigated depressive feelings, inner tension, intrusive thoughts of food, and the increased urge to be physically active, easing the way to recovery, yet had little influence on the patients’ personal commitment to remain at a low weight. Full recovery then require resolution of the individuals’ personal unresolved psychological conflicts through psychotherapy and frequently needs specialized treatment approaches to address psychiatric co-morbidities. AN might be conceptualized as a hereditary form of starvation resistance, facilitated by the effects of starvation on fitness allowing for an exceptionally intense personal commitment to perpetuate food restriction.